Aerodynamic and Stability Analysis of a Closed-Wing High-Altitude Pseudo-Satellite - Eleonora Riccio; Chiara Giaquinto; Vincenzo Rosario Baraniello; Giuseppe Persechino; Domenico Coiro (Engineering Proceedings, 2025)
The Italian Aerospace Research Centre (CIRA) is developing an unmanned stratospheric platform for Earth observation and telecommunications, known as a High-Altitude Pseudo-Satellite (HAPS). This paper presents an aerodynamic and stability analysis of a new closed-wing HAPS configuration. The design uses a hybrid approach, combining aerodynamic and aerostatic forces to achieve weight balance, with the stability analysis accounting for the buoyancy force applied at the center of volume of the structure. Following the initial design phase, which aims for an altitude of 20 km, a speed of 16 m/s, and a payload capacity of 20 kg, a suitable configuration using a NACA 0018 airfoil is selected. The aircraft lift–drag curve is evaluated using a stationary, incompressible Reynolds-Averaged Navier–Stokes (RANS) analysis with a k-<semantics>ω</semantics> SST turbulence model in OpenFoam. A detailed longitudinal and lateral-directional stability analysis is also conducted using OpenFOam and AVL software.